Fostering the Intercultural Learning in Drama Subject at Higher Education - Eripuddin Eripuddin; Pipit Rahayu; Rice Gus Gulita Sari (STAI Hubbulwathan Duri, 2025)
Intercultural learning plays a crucial role in preparing students for global engagement by fostering awareness of diverse cultures and enhancing communication across cultural boundaries. This study investigates the integration of intercultural learning within higher education, specifically in the English Department. A descriptive qualitative approach was employed, involving 23 fifth-semester English Department students selected through total sampling. A structured questionnaire was administered to assess students' cultural awareness, intercultural communication skills, and appreciation for diverse perspectives. The collected data were analyzed descriptively to evaluate students' intercultural competencies. The results indicate that 60.00% of students actively observe and recognize cultural differences in daily interactions. Additionally, 58.26% report a moderate level of confidence in communicating effectively in multicultural contexts, while 60.87% express a strong appreciation for diverse viewpoints and their contribution to enriching the learning experience. These findings suggest that integrating intercultural learning into the curriculum can significantly improve students' cultural sensitivity and communication skills. By promoting cultural understanding and inclusivity, such integration supports the development of more globally competent graduates.